2008
DOI: 10.1177/0891243207311046
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Paths to Teenage Political Participation

Abstract: This article examines how gender shapes the development, involvement, and visibility of teenagers as political actors within their communities. Based on ethnographic research with two high school student movement organizations on the West Coast, the author argues that gender impacts the potential for young people's political consciousness to translate into public, social movement participation. Specifically, the gendered ways in which youth conceptualize and negotiate parental power influences whether or not, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…For example, in a study that examined the factors influencing continued involvement in a campaign to register Black voters in Mississippi, McAdam (1988) found that youth who dropped out of the program attributed their lack of participation to parents' opposition to volunteering. Similarly, Gordon (2008) found that American youth—specifically, females—whose parents disapproved of protesting for political reasons were less likely to attend political rallies than those whose parents supported protesting. These young women reported changing their behavior in order to avoid conflicts with their parents and restore family harmony.…”
mentioning
confidence: 96%
“…For example, in a study that examined the factors influencing continued involvement in a campaign to register Black voters in Mississippi, McAdam (1988) found that youth who dropped out of the program attributed their lack of participation to parents' opposition to volunteering. Similarly, Gordon (2008) found that American youth—specifically, females—whose parents disapproved of protesting for political reasons were less likely to attend political rallies than those whose parents supported protesting. These young women reported changing their behavior in order to avoid conflicts with their parents and restore family harmony.…”
mentioning
confidence: 96%
“…To begin with, despite the gender neutrality of the subject of its official communication, i.e., 'youth' (see, for example, Palestinian Youth Network, 2008; Palestinian Youth Movement A; Palestinian Youth Movement, 2012b), gender equality is central in the PYM's pursuit of national liberation (Palestinian Youth Network, 2011, p. 3;Palestinian Youth Movement, 2012a). Contrary to what emerges in existing (albeit scant) literature discussing gender hierarchies in youth activism (see, for example, Coe et al, 2013;Gordon, 2008), and scholarship on gender and Palestinian nationalism and/or activism (see, for example, Younes, 2010;Amireh, 2003;Høigilt et al, 2013, p. 4;Fincham, 2012, pp. 127-8), gender does not appear to constitute an organizing principle affecting a PYM member's role and/or mobility within the movement.…”
Section: The Palestinian Youth Movement: Politics In and From The Diamentioning
confidence: 84%
“…Also considering that young people have limited participation in public policy-making due to the perception that they are immatured and inexperienced the presence of adult allies could be very useful in supporting young people in the public sphere. Adult mediators were found to be particularly important in promoting girls participation in political activities in a study by Gordon (2008) in which 'adult allies buffered the impact of parental worry on girls by serving as a crucial interface to concerned parents' (p. 48). Also, the role of adults in promoting children and young people's participation was again highlighted in a study by Gunn (2002) who argued that to increase youth participation in policy making 'young people should be supported by appropriately trained adults ... to identify areas for change and formulate a strategy to pursue these' (p. 219).…”
Section: Discussion Of Findingsmentioning
confidence: 99%